Linking weather variability and climatic pressure dipole in the Antarctic region of Amundsen – Bellingshausen – Weddell Seas - Pysarenko, Larysa; Savenets, Mykhailo; Pishniak, Denys (Ukrainian Antarctic Journal, 2025)
The climatic pressure dipole, formed by the Amundsen Sea Low (ASL) and the high-pressure area east of the Antarctic Peninsula (AP), is a major contributor to weather variability in West Antarctica and the peninsula region. Under the ongoing climate change, the role of this pressure configuration often remains uncertain. Using ERA5 reanalysis data for 1991–2022, we investigated the response of precipitation types and near-surface meteorological fields to variability in the climatic pressure dipole. A deepening eastward shift of the ASL increased snowfall over the Amundsen and Bellingshausen Seas, particularly near the low-pressure center itself, while precipitation near the AP tended to shift from solid to mixed or liquid phases. Strengthening of high pressure over the western Weddell Sea – especially when displaced closer to the AP – led to an overall decrease in precipitation, but with more frequent freezing rains and ice pellets over the northeastern AP. These relationships, however, were highly heterogeneous and exhibited strong seasonal features. Near-surface meteorological parameters showed weaker responses to the pressure dipole than precipitation. A deepened ASL generally lowered air temperature and saturation point over the eastern Bellingshausen Sea, while its eastward displacement produced warmer conditions across the study area. A high-pressure ridge east of the AP strongly influenced the thermal regime over the Weddell Sea and Dronning Maud Land, and was associated with intensified southerly and westerly winds in the southern part of the AP. Overall, this study enhances understanding of how surface meteorological conditions generally respond to atmospheric pressure variability in the region.